Analisis Kapasitas Hidraulik Saluran Drainase Menggunakan Pemodelan Storm Water Management Model (SWMM): Studi Kasus di Kecamatan Banguntapan - Muhamad Arifin; Cahyaning Kilang Permatasari (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Inundation is a major problem that frequently occurs in both residential areas and other urban zones, particularly in large cities. Flooding in residential areas is often caused by the failure of drainage channels to convey excess water. This condition commonly occurs when high rainfall intensity is not supported by adequate drainage capacity or when drainage channels are obstructed by solid waste. This study employs a mixed-methods approach, combining quantitative and qualitative methods. Identification was conducted through coordination with relevant stakeholders and direct observation of existing conditions at the study location. The analysis was carried out using hydraulic modeling of drainage channels with the SWMM 5.2 software. The results of the hydraulic modeling indicate that, in several locations, the drainage channel capacity is no longer sufficient and therefore requires capacity enlargement. Meanwhile, in locations where the channel capacity remains adequate, significant amounts of waste and sedimentation were found, causing blockages and reducing the effective capacity of the existing drainage system. To ensure the sustainability of the drainage system in Kapanewon Banguntapan, routine and periodic operation and maintenance activities are required, including rehabilitation of drainage channels that are already in deteriorated condition.